Hell hath no fury : a John Hawk western - West, Charles (West, Charles. John Hawk western., 2017)
When his brother and his young bride disappear deep into Sioux territory, Monroe Pratt convinces the legendary Indian scout John Hawk, who is known for delivering swift justice to anyone who stands in his way, to come out of retirement and rescue them.